2017
DOI: 10.12786/bn.2017.10.e4
|View full text |Cite
|
Sign up to set email alerts
|

Transcranial Direct Current Stimulation as an Alternative Treatment in Patients with Alzheimer's Disease

Abstract: Highlights• Transcranial direct current stimulation (tDCS) is a method of brain stimulation emerging as an alternative treatment of various neurological diseases.• Although tDCS affects cognitive function improvement in non-human studies, clinical trial results are still inconsistent.• This review provides an overview of the effects of tDCS on Alzheimer's disease. ABSTRACTTranscranial direct current stimulation (tDCS) is one of the brain stimulation techniques, which considered as an alternative treatment for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 83 publications
(86 reference statements)
0
2
0
Order By: Relevance
“…On the other hand, Bystad and colleagues (2016a) found no significant differences in memory improvement between active and placebo tDCS in patients with Alzheimer's disease. In Alzheimer's disease, studies using tDCS have shown inconsistent results ( Kim, 2016 ). In healthy individuals, tDCS is also associated with mixed results ( Tremblay et al., 2014 ).…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, Bystad and colleagues (2016a) found no significant differences in memory improvement between active and placebo tDCS in patients with Alzheimer's disease. In Alzheimer's disease, studies using tDCS have shown inconsistent results ( Kim, 2016 ). In healthy individuals, tDCS is also associated with mixed results ( Tremblay et al., 2014 ).…”
Section: Introductionmentioning
confidence: 99%
“…The anode increases cortical excitability while the cathode leads to cortical hypoexcitability [4,5]. tDCS has demonstrated efficacy in improving recognition memory performance [6][7][8] or face-naming association memory [9] in AD (Kim [10]). We therefore aimed to report the effects of this intervention on verbal cued recall performance in an individual with AD.…”
Section: Introductionmentioning
confidence: 99%